Altered Daytime Fluctuation Pattern of Plasminogen Activator Inhibitor 1 in Type 2 Diabetes Patients with Coronary Artery Disease: A Strong Association with Persistently Elevated Plasma Insulin, Increased Insulin Resistance, and Abdominal Obesity - Lalić, Katarina (Int J Endocrinol, 2015)
This study was aimed at investigating daily fluctuation of PAI-1 levels in relation to insulin resistance (IR) and daily profile of plasma insulin and glucose levels in 26 type 2 diabetic (T2D) patients with coronary artery disease (CAD) (group A), 10 T2D patients without CAD (group B), 12 nondiabetics with CAD (group C), and 12 healthy controls (group D). The percentage of PAI-1 decrease was lower in group A versus group B (4.4 ± 2.7 versus 35.0 ± 5.4%; P < 0.05) and in C versus D (14.0 ± 5.8 versus 44.7 ± 3.1%; P < 0.001). HOMA-IR was higher in group A versus group B (P < 0.05) and in C versus D (P < 0.01). Simultaneously, AUCs of PAI-1 and insulin were higher in group A versus group B (P < 0.05) and in C versus D (P < 0.01), while AUC of glucose did not differ between groups. In multiple regression analysis waist-to-hip ratio and AUC of insulin were independent determinants of decrease in PAI-1. The altered diurnal fluctuation of PAI-1, especially in T2D with CAD, might be strongly influenced by a prolonged exposure to hyperinsulinemia in the settings of increased IR and abdominal obesity, facilitating altogether an accelerated atherosclerosis.